1996
DOI: 10.1111/j.1553-2712.1996.tb03533.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Toxicity from Ocular Homatropine

Abstract: Toxidromes are well known to emergency physicians. An unclear or incomplete history and subtle findings on physical examination make the diagnosis of poisonings challenging. This article reports a patient who had an acute onset of visual hallucinations, pressured speech, and mania. Although she denied taking any medications, she was ultimately diagnosed as having anticholinergic toxicity. On further questioning of family members, it was discovered that she was being treated for anterior uveitis with 5% homatro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…11 One case report describes classic systemic antimuscarinic poisoning after ophthalmic administration of homatropine for the treatment of anterior uveitis. 12 In choosing a dose of homatropine for study, we found that doubling the dose of homatropine (20 mg/kg vs. 10 mg/kg of atropine sulfate) was equivalent to standard atropine sulfate in preventing death in our previous work in the laboratory as well as in this current experiment. 8 Our study revealed a significant survival benefit for rats treated with standard atropine sulfate (10 mg/kg), ophthalmic homatropine (20 mg/kg), and ophthalmic atropine sulfate (10 mg/kg).…”
Section: Discussionmentioning
confidence: 57%
“…11 One case report describes classic systemic antimuscarinic poisoning after ophthalmic administration of homatropine for the treatment of anterior uveitis. 12 In choosing a dose of homatropine for study, we found that doubling the dose of homatropine (20 mg/kg vs. 10 mg/kg of atropine sulfate) was equivalent to standard atropine sulfate in preventing death in our previous work in the laboratory as well as in this current experiment. 8 Our study revealed a significant survival benefit for rats treated with standard atropine sulfate (10 mg/kg), ophthalmic homatropine (20 mg/kg), and ophthalmic atropine sulfate (10 mg/kg).…”
Section: Discussionmentioning
confidence: 57%
“…Cases of anticholinergic poisoning following the administration of topical eye drops containing atropine or atropine-like substances have been previously reported (1,(3)(4)(5). When a patient has nonreactive dilated pupils, tachycardia, flushed skin, dry mucosa, hyperthermia, urinary retention, and changes in consciousness, anticholinergic poisoning should be considered (3,4,6). Decreased sweat levels, reduction in bowel sounds, visual and auditory hallucinations, delirium, seizures, coma, and even death may also represent part of the anticholinergic toxidrome (Table 1) (6).…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain similar results in our study, the homatropine dosing requirement was twice that of atropine. Classic antimuscarinic poisoning has been reported with systemic poisoning of homatropine after ophthalmic administration for the treatment of anterior uveitis [14].…”
Section: Discussionmentioning
confidence: 99%